دور الاستثمار الصناعي في تحقيق التنمية المحلية في تيسمسيلت - دراسة القدرات والفرص الاستثمارية في القطاع الصناعي لولاية تيسمسيلت –: the role of industrial investment in achieving local development in Tissemsilt - study the state’s investment capabilities and opportunities in the industrial sector in the state of Tissemsilt - ربحي فاطمة (Journal of North African Economies, 2025)
This study aims to highlight the role of industrial investment in achieving local development in Tissemsilt, thanks to the investment projects embodied in the state of Tissemsilt, and to understand its role in achieving local development by studying the capacities and investment opportunities of the state in the industrial sector, especially with the recent launch of the local development supplementary programme for the state, which affected all sectors through the completion of projects aimed at breaking the isolation of this young state. The study concluded with the following conclusions: The industrial sector in the state of Tissemsilt has a major role in achieving local development, especially with regard to the economic role of small and medium enterprises in the field of manufacturing, and the state has witnessed an improvement in the implementation of various investment projects in several fields, including industry, tourism, agriculture and health, within the framework of the proposed supplementary programme to support local development in the state of Tissemsilt.